Effects of a whole body compression garment on recovery after a heavy resistance - Arbabi, A. (Turkish Journal of Sport and Exercise, 2015)
This study aimed to investigate the effects of wearing a whole body compression garment on recovery from a typical heavy resistance training workout in resistance trained men and women. Fourteen men (mean ± SD: age, 23.0 ± 2.9 years) and fourteen women (mean ± SD: age 23.1 ± 2.2 years) who were highly resistance trained gave informed consent to participate in the study. A within-group (each subject acted as their own control), balanced, and randomized treatment design was used. Nutritional intakes, activity, and behavioral patterns (e.g., no pain medications, ice, or long showers over the 24 hours) were replicated 2 days before each test separated by 72 hours. An 6-exercise whole body heavy resistance exercise protocol using barbells (10 repetition of 3 sets at 70% of one- repetition maximum, 2.0 minute rest) was performed after which the subject showered and put on a specific whole body compression garment one designed for women and one for men (CG) or just wore his/her normal noncompression clothing (CON). Subjects were then tested after 24 hours. Dependent measures included sleep quality, vitality rating, resting fatigue rating, muscle soreness, muscle swelling via ultrasound, reaction movement times, bench throw power, countermovement vertical jump power, and serum concentrations of creatine kinase (CK) measured from a blood sample obtained via venipuncture of an arm vein. We observed significant (p= 0.05) differences between CG and CON conditions in both men and women for vitality (CG , CON), resting fatigue ratings (CG , CON), muscle soreness (CG , CON), ultrasound measure swelling (CG , CON), bench press throw (CG .CON), and CK (CG, CON). A whole body compression garment worn during the 24-hour recovery period after an intense heavy resistance training workout enhances various psychological, physiological, and a few performance markers of recovery compared with noncompressive control garment conditions. Wearing a CG appears to help in the recovery process after intense heavy resistance training in men and women.